Low Temperature Thermodynamics. The excess Gibbs function and the volumes of mixing for the system methane + - Stoeckli, Fritz; Staveley, L. A. K. (My University, 1969)
The excess Gibbs function Ge and the excess volumes of mixing I/e have been measured at the methane triple point (90.68 K) for the system methane+propane. They were compared with McGlashan's recent theory for mixtures of molecules of different sizes.